Pengaruh Kecerdasan Matematis, Media Pembelajaran, Minat dan Hasil Belajar Terhadap Tingkat Pemahaman Akuntansi Siswa SMKN 1 Jombang - Thoriqil Mun'im, Muhammad; Listiadi, Agung (Politeknik Negeri Ambon, 2025)
This study intends to analyse the influence of mathematical intelligence, learning media, interest and learning outcomes on students’ accounting comprehension ability at the vocational secondary level. The research was carried out using a quantitative method, determining the sample using simple random sampling in the student population of SMKN 1 Jombang, as many as 140 students and a sample of 104 students in grade XI of SMKN 1 Jombang. The researcher used questionnaires and documentation to collect and analyse data with linear regression tests through the SPSS version 26 application. The results of the study revealed (1) Students’ mathematical, logical intelligence, learning media, interests and learning outcomes of basic accounting students with test results F 0.049 < 0.05 showed a significant influence on the improvement of accounting understanding of grade students (2) Mathematical, logical intelligence partially had an influence of 21.1% on the level of accounting understanding of students (3) The learning outcomes of basic accounting partially had a significant influence of 44.5% on the level of accounting understanding students (4) Learning media did not have a significant influence with the results of the t-test 0.883 > 0.05 on students’ level of accounting understanding (5) Learning interest partially had a significant influence of 13.4% on students’ level of accounting understanding.Keywords: mathematic logics, learning media, learning interests, learning outcomes, students’ accounting understanding.